Occupational Stress and Coping Strategies Among Teachers in Nepal (THE ACADEMIA, 2026)
This article explores the multifaceted issue of occupational stress among teachers in Nepal, focusing on systemic stressors and integrated management strategies. It is guided by two primary objectives: to identify the systemic factors causing occupational stress among teachers, and to explore integrated strategies for enhancing teacher well-being and professional sustainability. Employing a qualitative research design within an interpretivist paradigm, the study has utilized purposive sampling to select secondary school teachers from Kathmandu district. Data were collected through semi-structured interviews and focus group discussions, and were analyzed using thematic analysis. The findings reveals  five interconnected themes: overwhelming professional demands characterized by excessive workloads, large class sizes, and administrative burdens; erosion of professional self-worth stemming from lack of recognition and support; embodied physical and psychological consequences including chronic fatigue and emotional exhaustion; fragmented institutional support systems with limited formal mechanisms; and individual coping strategies operating within structural constraints. The study concludes that while teachers demonstrate resilience through personal coping mechanisms, sustainable stress management requires a holistic approach integrating organizational interventions—such as fair workload distribution, supportive leadership, and structured well-being programs—with institutional support systems. These findings underscore the necessity for systemic reforms in Nepalese educational institutions to address the structural sources of stress and promote teacher well-being, thereby enhancing educational quality and professional sustainability.